Virtual Group Meaning Centered Psychotherapy for Palliative Care Patients - Taylor, Erin; Chesak, Sherry; Tofthagen, Cindy; Applebaum, Allison; Pachman, Deirdre (Journal of pain and symptom management, 2025)
1. To understand the role of meaning centered psychotherapy in treating existential and psychological distress in patients with serious illness. 2. To learn that it was feasible and acceptable to deliver a virtual group-meaning-centered psychotherapy program to patients with a spectrum serious illness in an outpatient palliative care clinic. Virtual Group Meaning Centered Psychotherapy (MCP) is feasible to implement in an outpatient palliative care clinic. Participants valued the connection with other patients with a spectrum of serious illnesses and most reported that the program enhanced meaning and improved mood. Virtual MCP groups may be an important addition to outpatient palliative care offerings to support psychological and existential distress. Patients living with serious illness often suffer from existential distress. Meaning centered psychotherapy (MCP) is a manualized, brief, structured psychotherapeutic intervention to help patients suffering with loss of meaning around illness (1). The purpose of this program evaluation project was to assess the feasibility and acceptability of a virtual group MCP program for patients with serious illness in a clinical setting. Potential participants included patients receiving care in an outpatient palliative care clinic who were experiencing psychological and/or existential distress. The MCP program included 7-8 group sessions via a real-time audiovisual platform. Sessions were facilitated by a palliative care physician and social worker trained in MCP. Participants completed a program evaluation after the final session. Thematic analyses were conducted on additional comments provided by participants. 36 patients enrolled and 30/36 completed the program. 24 had advanced cancer, 10 had neurodegenerative disease, and 2 had other serious illnesses. Twenty participants completed the program evaluation. Patients reported that they were satisfied with the experience and would recommend the therapy to others (20/20). The majority indicated that participating in the group enhanced sense of meaning (15/20), helped them cope better with their illness (14/20), and improved their mood (16/20). The majority indicated the virtual component was acceptable (19/20). Themes identified with qualitative analysis included: support/connection with other group members, skilled facilitation, topics and discussions enhanced sense of meaning, contributed to self-compassion, and appreciate program structure. It was feasible and acceptable to deliver a virtual group MCP program to patients with a spectrum of serious illnesses in an outpatient palliative care clinic. Patients indicated that the program had a positive impact on meaning, helped them cope better, and improved their mood. Virtual MCP groups may be an important addition to outpatient palliative care offerings to support psychological and existential distress. 1.Breitbart W, Rosenfeld B, Pessin H, et al. Meaning-Centered Group Psychotherapy: An Effective Intervention for Improving Psychological Well-Being in Patients With Advanced Cancer. J Clin Oncol. 2015